Preparation and characterization of sulfur-vinylbenzyl chloride polymer under optimized reaction conditions using inverse vulcanization - Abbasi, A. (Elsevier Ltd, 2021)
Inverse vulcanization offers a new method to make value to this cheap and highly abundant sulfur to produce sulfur-based polymers for different applications. However, most of the research done so far dealt with the characterization of the polymers or their efficiency in certain applications. Here, 4-vinylbenzyl chloride (VBC) is reacted with sulfur under optimized reaction conditions to produce linear sulfur-based polymer. Response Surface Methodology (RSM) is employed to optimize the reaction conditions in terms of reaction temperature, reaction time, and initial sulfur content. The properties of the polymer produced under optimized conditions are then evaluated using proton nuclear magnetic resonance (1H NMR), CHNS elemental analysis, thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), Fourier transform infrared spectroscopy (FTIR), powder X-Ray diffraction (PXRD), and field emission scanning electron microscopy (FESEM). The formation of the polymer and full conversion of the monomers were confirmed by NMR and CHNS analysis. The S/VBC polymer showed a uniform morphology and smooth surface. The polymer demonstrated an amorphous structure with a low Tg (3.7 °C), high thermal stability (205 °C), and great stability against depolymerization by time. The S/VBC polymer is significant due to its ability for post-functionalization which makes it possible to introduce new applications to sulfur-based polymers. © 2020 Elsevier Ltd